Hydrologic Variability: Implications for Local Management in Nepal - Dixit, Ajaya; Moench, Marcus (Water Nepal, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> The authors argue that vulnerability present inherent challenge to water management throughout South Asia. Conventional water management strategies attempt to reduce the inherent variability in water availability by controlling flows, developing storage facilities and diversifying water supply sources. They argue that the first two strategies are both inadequate and risky in South Asian context. Variability and the characteristics extreme events have embedded uncertainly that has fundamental implications for water management strategies. Their paper also document some of the key factors responsible for variability of hydrologic systems in South Asia s well as the uncertainty that underlies water management with focus on Nepal's Himalayan region. Keywords: water management; diversifying water supply sources; water management strategies; Nepal Water Nepal Vol. 12, No. 1&2, 2006 Page: 227-260